2013
DOI: 10.4236/ojo.2013.32024
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Outcome of Total Knee Replacement in Young Patients: A 10-Year Matched Case Control Study

Abstract: We present the results of a prospective study on the functional outcome from total knee replacement (TKR) in young versus old patients. American Knee Society and pain scores over ten years post TKR were compared using a cohort of young patients (≤55 years) and a control group of patients ≥56, matched for ASA, body mass index and preoperative condition. A total of 24 young and 24 older knees were analysed. All scores improved significantly over time. There was no statistical differences over 10 years in pain (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Spinal anesthesia and sedation was the most common type of anesthesia used with the majority of patients staying around a week. While this corroborates with previous figures [6,[15][16][17], a contradictory result [18] is that there was no association between any of the parameters studied and length of stay.…”
Section: Resultssupporting
confidence: 91%
“…Spinal anesthesia and sedation was the most common type of anesthesia used with the majority of patients staying around a week. While this corroborates with previous figures [6,[15][16][17], a contradictory result [18] is that there was no association between any of the parameters studied and length of stay.…”
Section: Resultssupporting
confidence: 91%
“…We present the first early clinical, radiological and patient reported results for the PFCSCC TKA. We have previously reported on the medium-to long-term follow up of the PFC Sigma TKA [9][10][11][12][13]. The design of the PFC Sigma Cobalt Chrome TKA incorporates a number of minor modifications from the PFC Sigma TKA and these initial results show that at three years post-operatively, the prosthesis survival rate stands at 97.6% with revision for any reason and 99.6% with revision for aseptic failure.…”
Section: Discussionmentioning
confidence: 99%
“…Some specialist centres have reported survivorship between 87 to 99% in young patients undergoing a cemented total knee replacement at a medium-term follow up between 6 to 14 years [ 80 82 ]. In a case matched series it was also suggested that younger patients achieve similar results from TKA, in terms of pain and function, which are comparable and even superior to older patients when matched for ASA, diagnosis, and BMI [ 83 ]. Therefore, a younger age should not preclude patients from having a total knee replacement although in cemented components there still remains general anxiety about the osteolysis and loosening as a result of wear debris from the perceived multiple cyclical loading.…”
Section: Total Knee Replacementsmentioning
confidence: 99%